INFLUENCE OF TRAINING ON ANAEROBIC POWER AND CAPACITY OF UPPER AND LOWER LIMBS IN YOUNG GRECO-ROMAN WRESTLERS - Dariusz Gierczuk; Elżbieta Hübner-Woźniak; Barbara Długolęcka (Termedia Publishing House, 2012)
The aim of the present study was to examine the effect of training on selected markers of anaerobic capacity of upper and lower limbs in male, Greco-Roman wrestlers from 16 to 19 years of age. The study was conducted four times at one-year intervals on the same group of male competitors (n=12). Every year at the beginning of the second preparatory period all wrestlers performed arm cranking and leg cycling 30 s Wingate tests. The relative peak and mean power of upper limbs were higher in 17-, 18-, and 19-year-old wrestlers compared to 16-year-old ones, but were similar in 17- and 18-year-old athletes. The highest peak and mean power of legs were found in 19-year-old wrestlers. In 18-year-old athletes, the peak power was lower than in 17-year-olds and was similar to 16-year-old wrestlers. The relative mean power in the group of 18-year-old athletes was lower compared to 16- and 17-year-old ones, but it was similar in 17- and 19-year-old wrestlers. Changes in the levels of the relative peak and mean power of upper and lower limb muscles in wrestlers occurred at different periods between the age of 16 and 19. However, it seems that inappropriately chosen training loads may reduce short-term power outputs despite age correct increase in anthropometric parameters. Wrongly applied training did not bring positive effects and could inhibit, for some time, the natural development of power in young wrestlers.